Water hyacinth as a possible bioenergy resource: A case of Lake Victoria, Kenya. Issue 2 (February 2019) - Adwek, George; Julius, Gane; Shen, Boxiong; Lan, Meichen; Cecilia, Kemunto M.; Yabo, Abel C.
Abstract: Currently, climate change and its impacts are driving the development of renewable energy resources globally. There is a growing quest to widen the supply of biomass resources for bioenergy production. In this paper, we interviewed local people to elicit perceptions regarding current and potential uses of water hyacinth, Eichhornia crassipes, which grows in large quantities at the Lake Victoria region in Kenya. The aim was to determine peculiar problems and what possibilities lay in bio renewable energy production from the resource. Most of the respondents favoured development of the water hyacinth into viable commercial products, mainly due to its various negative effects such as: impact on water quality and fishing businesses as well as interference with irrigation systems. Our research however, observed that promotion of commercial bioenergy production from the water hyacinth may however be faced with some competition due to existing livelihood factors (e.g. source of organic fertilizer for crop production, craftwork, etc.). From the findings, we conclude that because the water hyacinth widely grows in this region, there is an opportunity to expand biomass for bioenergy in the region. This however, will require a participatory approach; to consider the livelihood values, as well as developing of affordable biofuel products. The results are expected to inform environmental/energy planning and decisions, particularly regarding the negative impacts of the water hyacinth and its potential values (e.g. as a bioenergy resource).